Facing Challenges: Strategies of Female Farmers in Rokan Hulu Regency in Balancing Work and Family Life - Hendry Kurniawan; Erik Estrada; Defidelwina (International Journal of Economic and Tourism Research, 2025)
This study explores the strategies employed by female farmers in Rokan Hulu Regency, Indonesia, in balancing dual roles as agricultural workers and homemakers. Using a qualitative phenomenological approach, in-depth interviews were conducted with 16 female farmers across 13 villages and 1 urban ward in Rambah District. The research identifies the underlying motivations for assuming dual roles, including economic necessity, family tradition, and personal identity, while also examining the types of work-family conflict experienced. Findings reveal that the most common conflicts are time-based, emotional, and behavioral, where women struggle to manage domestic duties alongside physically demanding agricultural work. To address these challenges, participants adopt adaptive strategies such as strict time management, role negotiation within the household, utilization of labor-saving tools, and reliance on community support networks. The study is grounded in Role Theory and the Work-Life Balance framework, highlighting how female farmers constantly negotiate conflicting demands in socio-economically constrained environments. The findings underscore the importance of gender-sensitive agricultural policy, particularly in providing support services such as childcare, flexible work arrangements, and psychosocial assistance. This research contributes to broader discourses on gender, rural labor, and agrarian resilience, and emphasizes the urgent need for structural interventions to alleviate the burden of work-family conflict faced by women in traditional agricultural systems.